2022
DOI: 10.1186/s40662-022-00292-4
|View full text |Cite
|
Sign up to set email alerts
|

Complement C3 deficiency alleviates alkylation-induced retinal degeneration in mice

Abstract: Background It has been found that the extensive use of anticancer drugs containing DNA-alkylating agents not only target cancer cells but also cause retinal inflammation through toxic intermediates. Complement C3 (C3) is a core component of the complement activation pathway, and dysregulation of the complement pathway is involved in several retinal degenerative diseases. However, whether C3 plays a critical role in alkylation-induced retinal degeneration is unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Among the common DEGs, several genes might play a role in the response to DNA damage. Du et al [41] found that the activation of complement C3 contributed to retinal DNA damage and C3 deficiency alleviated alkylation-induced retinal degeneration in mice. Raso et al [42] reported that Isg15 upregulation promoted DNA replication fork progression, leading to extensive DNA damage and chromosomal aberrations in a human osteosarcoma cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Among the common DEGs, several genes might play a role in the response to DNA damage. Du et al [41] found that the activation of complement C3 contributed to retinal DNA damage and C3 deficiency alleviated alkylation-induced retinal degeneration in mice. Raso et al [42] reported that Isg15 upregulation promoted DNA replication fork progression, leading to extensive DNA damage and chromosomal aberrations in a human osteosarcoma cell line.…”
Section: Discussionmentioning
confidence: 99%
“…While their work corroborated that uncontrolled activation of C3, investigated through mice deficient in complement factor H (CFH), was associated with negative effects on retinal aging, including amyloid β deposition and inflammation, complete absence of C3 also had deleterious effects on retinal aging. Later studies involving complete C3 ablation have described a positive impacts of deletion, including decreased retinal degeneration [ 112 , 113 ]. Furthermore, exogenous delivery of C3 to murine RPE produces functional and anatomic changes resembling AMD [ 114 ].…”
Section: Targeting Complement Pathways In Retinal Diseasementioning
confidence: 99%
“…Modulation of complement cascade activity in general, and specifically downregulation of C3, has been linked to increased photoreceptor survival and improved visual function in a C3 knockout mouse model. 27 Immunohistochemistry of both primate and human retinas has shown C3 deposition in the choriocapillaris and, perhaps more surprisingly given the blood-retina barrier, also in the outer photoreceptor segments. [28][29][30][31] The protective effect of C3 inhibition could therefore be indirect at the choriocapillaris level, or direct at the level of the photoreceptors.…”
Section: Proposed Mechanism Of Pegcetacoplan and Ga Pathophysiologymentioning
confidence: 99%